2011
DOI: 10.1159/000329806
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase I/II Study of Docetaxel, Cisplatin and Fluorouracil Combination Chemotherapy in Patients with Advanced or Recurrent Squamous Cell Carcinoma of the Esophagus

Abstract: Objective: Esophageal squamous cell carcinoma (ESCC) is refractory to current therapeutic regimens and more effective therapies are imperative. To this end, we conducted a multicenter phase I/II trial of docetaxel, cisplatin, and fluorouracil (DCF) combination chemotherapy for ESCC. Methods: The study subjects were 46 patients with advanced or recurrent ESCC. Treatment included docetaxel at 60, 70, and 75 mg/m2, cisplatin at 70 mg/m2 on day 1, and daily fluorouracil at 700 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 45 publications
4
78
3
Order By: Relevance
“…10,11 More trials with DCF therapy in esophagus carcinoma have been reported. 8,9,12,13 DOC is a semisynthetic taxoid derived from the European yew tree, Taxus baccata. The taxanes enhance polymerization of tubulin into stable microtubule formation and inhibit their tubulin depolymerization by blocking the cell cycle in metaphase, anaphase, and interphase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 More trials with DCF therapy in esophagus carcinoma have been reported. 8,9,12,13 DOC is a semisynthetic taxoid derived from the European yew tree, Taxus baccata. The taxanes enhance polymerization of tubulin into stable microtubule formation and inhibit their tubulin depolymerization by blocking the cell cycle in metaphase, anaphase, and interphase.…”
Section: Discussionmentioning
confidence: 99%
“…Yamasaki et al reported that the major toxicity of DCF, repeated every 3 weeks at a dose of DOC 70 mg/m 2 , CDDP 70 mg/m 2 , and 5-FU 700 mg/m 2 , was myelosuppression and that the frequencies of grade 3/4 leukopenia and neutropenia in a phase II study were 72.5% and 90%, respectively. 9 Ando et al reported toxicity with PF therapy when repeated every 3 weeks after surgery within 2 months. The dose levels were CDDP 70 mg/m 2 and 5-FU 700 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination DCF has been used to treat unresectable and recurrent SCC of the esophagus and is well tolerated with high response rates (33,34). Recently, preoperative chemotherapy using DCF was reported to have increased survival rate benefits for patients with resectable and advanced esophageal cancer (35).…”
Section: Univariate Analysismentioning
confidence: 99%
“…Recently, some groups have reported that the addition of docetaxel to CF (DCF) was effective for patients with gastric cancer and head and neck cancer (11,12). Taking these results into account, several studies evaluating the efficacy and safety of DCF regimen for metastatic or recurrent esophageal cancer have been reported (13)(14)(15)(16). In these reports, the dose and schedule of DCF were as follows: docetaxel (50-70 mg/m 2 , Day 1), cisplatin (60-70 mg/m 2 , Day 1) and fluorouracil (600-800 mg/m 2 , Days 1-5) every 3-4 weeks.…”
Section: Introductionmentioning
confidence: 99%